การศึกษาความเป็นไปได้ในการใช้วิธีวัดสภาพต้านทานไฟฟ้าตรวจหาโครงสร้างธรณีวิทยาที่มีลักษณะเป็นแอ่ง - วรวุฒิ โลหะวิจารณ์ (มหาวิทยาลัยสงขลานครินทร์, 2024)
Ten Schlumberger sounding with the maximum current electrodes separation of 2 km were carried out in the Krabi basin. The aim of the study was to delineate the of the basin. boundaries Results from the study show that the resistivity of the sediment in the basin is less than 20 ohmm and there are lateral changes in resistivity to greater than 120 ohmm and to greater than 40 ohmm at the western and the eastern rims of the basin. The boundaries determined from the resitivity measurement agree with those determined agree with those determined from the gravity anomaly and with the geological boundaries. However, the vertical boundary of the basin could not be determined from the present study. This probably dues to a small resistivity contrast, between the basin sediment and the bedrock or a weak current source.